Exosomes in Head and Neck Squamous Cell Carcinoma - Xiao, Cheng; Song, Fang; Zheng, Yu Long; Lv, Jiong; Wang, Qiang Feng; Xu, Nong (Frontiers in Oncology, 2019)
Exosomes are small membranous vesicles that contain proteins, lipids, genetic material, and metabolites with abundant information from parental cells. Exosomes carry and deliver bioactive contents that can reprogram the functions of recipient cells and modulate the tumor microenvironment to induce pathological events through cell-to-cell communication and signal transduction. Tumor-derived exosomes (TDEs) in head and neck squamous cell carcinoma (HNSCC) are involved in most aspects of cancer initiation, invasion, progression, immunoregulation, therapeutic applications, and treatment resistance. In addition, HNSCC-derived exosomes can be used to obtain information on diagnostic and therapeutic biomarkers in circulating blood and saliva. Currently, the biology, mechanisms, and applications of TDEs in HNSCC are still unclear, and further research is required. In this review, we discuss various aspects of exosome biology, including exosomal components, exosomal biomarkers, and molecular mechanisms involved in immunoregulation, cancer metastasis, and therapy resistance. We also describe recent applications to update our understanding of exosomes in HNSCC.